APLICACIÓN DEL SISTEMA DE CONTROL INTERNO BASADO EN EL MODELO COSO I COMO HERRAMIENTA DIDÁCTICA QUE ESTABLECE LA METODOLOGÍA A APLICAR PARA EVALUACIONES DE CONTROL INTERNO - Jaramillo Mediavilla, Lorena (Revista Ecos de la Academia, 2021)
The present investigation deals with the Application of the Internal Control System based on the COSO I Model as a didactic tool that establishes the methodology to be applied for Internal Control evaluations. The Accounting Unit of the Financial Management of the Technical University of North, in order to carry out a correct use of public resources, this study starts from the need to evaluate each of the internal control components and determine possible risks that may arise in the processes carried out in the Accounting Unit, in order to mitigate them to achieve the objectives: operational, Financial Information; and, Compliance with legislation and regulations that govern public institutions. This research is quantitative with a bibliographic, descriptive and field approach. The results obtained indicate that the general level of confidence is 78%, as a result of the comprehensive evaluation of the accounting unit’s internal control system. In conclusion, a high confidence rating was determined through an average of the results of the five evaluated components.